2015
DOI: 10.1016/j.jpowsour.2014.11.098
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nickel doped anatase titanate as high performance anode materials for lithium ion batteries

Abstract: Novel Ni-doped titanate derived from protonated layered titanate has been fabricated via a simple ion-exchange process at room temperature. The as-synthesized product was calcined at 400 ºC for 3h to obtain the Ni-TiO 2 (anatase). The crystal structure of Ni-TiO 2 was studied by X-ray diffraction (XRD) and the surface chemistry was studied by X-ray photoelectron spectroscopy (XPS). It was found that doped nickel ions had inhibition effects on the crystallization of TiO 2 during calcination. The electrochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 39 publications
2
31
0
1
Order By: Relevance
“…The high reversible capacity, outstanding cycling performance and good rate capability of Cr-TiO 2 is not only ascribed to the characteristic nanostructure which contributes to faster di®usion of electrolyte, 29 but also the high conductivity due to the p-type conductivity of TiO 2 via the generation of holes 20 and the high lithium storage capacity of Cr 2 O 3 (1058 mAh g À1 ) which is helpful for improving the capacity of TiO 2 . 15,30 In order to gain insight into the e®ect of the Crdoping, EIS tests were implemented. As shown in Fig.…”
Section: -5mentioning
confidence: 99%
See 1 more Smart Citation
“…The high reversible capacity, outstanding cycling performance and good rate capability of Cr-TiO 2 is not only ascribed to the characteristic nanostructure which contributes to faster di®usion of electrolyte, 29 but also the high conductivity due to the p-type conductivity of TiO 2 via the generation of holes 20 and the high lithium storage capacity of Cr 2 O 3 (1058 mAh g À1 ) which is helpful for improving the capacity of TiO 2 . 15,30 In order to gain insight into the e®ect of the Crdoping, EIS tests were implemented. As shown in Fig.…”
Section: -5mentioning
confidence: 99%
“…[10][11][12] However, relatively low theoretical capacity (168 mAh g À1 ) and poor electrical conductivity have become an obstacle for TiO 2 as a power battery anode material in the future. 10,11 To circumvent these obstacles, a variety of strategies have been devoted to improve lithium storage capacity and electrical conductivity of TiO 2 , such as nanoscale materials 13 and carbonbased composites, 13,14 especially with metal doping nanostructured materials 15 usually have good electrochemical performances.…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that heteroatoms substituted into the TiO 2 lattice can create dopant energy levels and fully modify the electronic structures such as B, N, S, Mn, Ni, and Sn. 13,18,14,17,24 On one hand, some interstitial oxygen defects and vancancies, or titanium vacancies are created as a result of the difference of ionic radius and electronegativies, which significantly improves the electrical conductivity and decreases the charge transfer resistance. On the other hand, the doping Mo 6+ ions with a larger radius (0.068 nm) can induce the increase of unit cell volume in the TiO 2 crystal structure as well as lattice distortion (Fig.…”
Section: Li-ion Storage Performance Referencesmentioning
confidence: 99%
“…incorporation into the crystal structure is a promising way for TiO 2 modification. Doping in small amounts leads to the charge redistribution in the lattice, increase in conductivity, facilitation of the Li + diffusion, creation of defects [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…incorporation into the crystal structure is a promising way for TiO 2 modification. Doping in small amounts leads to the charge redistribution in the lattice, increase in conductivity, facilitation of the Li + diffusion, creation of defects [9][10][11].In the present work, an inexpensive template sol-gel method is reported for the synthesis of nanostructured Zr-doped (1 at.%) TiO 2 (anatase) as a promising LIB anode.Zr-doped TiO 2 was synthesized by stepwise hydrolysis of a solution mixture of TiCl 4 (2 g L À1 ) and ZrOCl 2 (0.1 g L À1 ), by precipitation on the surface of a carbon fiber template. As the template Busofit-TM-4 fiber manufactured by the Svetlogorsk Chemical Fiber Plant (Belarus) was used.…”
mentioning
confidence: 95%